ADAMTS13 : Biology and Disease - Rodgers, George M. (Springer International Publishing : Imprint: Springer, 2015)
This comprehensive volume discusses the protease ADAMTS13, summarizing the current status of basic and clinical research. The nine authoritative chapters begin with a historical perspective followed by exploration of the biochemistry and structure-function relationships of ADAMTS13 as well as its normal function in hemostasis (cleavage of von Willebrand factor). Emerging research themes for ADAMTS13 are covered, including its potential role in angiogenesis and other aspects of cell biology. Additional topics include laboratory assays for ADAMTS13, inherited ADAMTS13 deficiency, and acquired ADAMTS13 deficiency. A chapter on related thrombotic microangiopathic (TMA) disorders examines the differences between TMAs associated with ADAMTS13 deficiency and those not associated with ADAMTS13 deficiency. A final chapter reviews the preliminary information on emerging aspects of ADAMTS13, such as the status of recombinant ADAMTS13 products and their potential utility.   Comprehensive in its exploration of the ADAMTS13 protease in disease, ADAMTS13: Biology and Disease is a significant resource for clinical hematologists, transfusion medicine physicians, and researchers interested in hemostasis, vascular biology, biochemistry, and metalloproteases.